From Cuenca to Queens : an anthropological story of transnational migration - Miles, Ann (Ann M.) (University of Texas Press, 2004)
Discussions of transnational migration rarely spare time for the individual stories which can be told by real people. This volume does just that, following the journey of Vicente Quitasaca from Cuenca in Ecuador to New York City. Ann Miles assesses the impact on his life & on his family.